People’s Role as Victims in State Financial Corruption - Adi Darmawansyah (International Journal Labs, 2023)
In positive law in Indonesia related to public participation as victims in corruption crimes is still not regulated in the criminal law. In particular, corruption of state financial losses has harmed society. Many of the Court's Rulings only focus on the return of state losses to the state treasury, however, the real victims are the people who have been charged with the crime of corruption who do not get access to justice from the sentencing of the court. The state must access the return of state losses to the public as victims of corruption crimes Indonesia has ratified the United Nations Convention Against Corruption/UNCAC convention through Law Number 7 Tahun 2006 concerning ratification of the United Nations Convention on Anti-Corruption has not fully provided space for victims in this case the community to be able to demand compensation, restitution, compensation for corruption cases. This research is normative juridical by examining the formulation provisions in Law No. 31 of 1999 concerning the Eradication of Corruption Crimes jo. Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Corruption Crimes and ratifying the United Nations Convention Against Corruption/UNCAC convention through Law Number 7 of 2006 on ratification of the United Nations Convention on Anti-Corruption.